REDUCTION OF THE PRODUCTION COST. EXPERIENCE OF THE COSTS REDUCTION AT RUP “BMZ” - S. S. Sereda (Литьë и металлургия)
The method of the daily operative monitoring of the costs for reduction of net cost and reinforcement of control on the costs has been applied for the first time in 2003 in RB at RUP “BMZ”, that allowed for the enterprise to control the costs in regime of real time.